6ER-010 Focus on hcv treatment based on second-generation direct-acting antiviral agents (daas-2): comparing national and local prescribing trends. (2nd March 2018) - Inserra, C; Zovi, A; Scalzi, V; Zampogna, L; Vimercati, S; Piacenza, M; Zerega, G
Abstract : Background: Since the beginning of 2014, an increasing number of second-generation direct-acting antiviral agents (DAAs) have been approved in Italy for treating chronic hepatitis C virus (HCV) improving patients' perspectives and increasing treatment outcomes. In order to achieve high-quality treatment with these costly drugs, DAA-2 prescriptions are subject to strict rules (specific drug for specific patient characteristics and virus genotype) and intense monitoring. Purpose: The aim of the work was to compare national 1 and local prescribing trends. Material and methods: Local electronic monitoring prescriptions of DAA-2 made from January 2015 to February 2017 were extracted from the national monitoring prescriptions database. The number of prescriptions for each DAA-2 was extracted. Qualitative and quantitative presentation of local data were adapted in order to make them comparable to available national data. Both local and national monthly average drug prescription for each DAA-2 was assessed, considering the number of months of commercialisation of each DAA-2. Local and national prescribing trends were assessed and compared. Results: 1026 electronic local monitoring prescriptions were analysed. Treatments were: sofosbuvir (31.3%), ledipasvir/sofosbuvir (20.9%), ombitasvir/paritaprevir/ritonavir (25.9%–20.4% in monotherapy; 5.5% in association with dasabuvir), daclatasvir (15%) and simeprevir (6.9%). The national and local monthly average of prescriptions was respectively: 345 and 12 (sofosbuvir), 1084 and 10 (ledipasvir/sofosbuvir), 680 and 7 (sofosbuvir/daclatasvir), 303 and 3 (simeprevir), 615 and 13 (ombitasvir/paritaprevir/ritonavir-dasabuvir). National prescribing trend (listed in ascending order) was: simeprevir, sofosbuvir, ombitasvir/paritaprevir/ritonavir-dasabuvir, sofosbuvir/daclatasvir and ledipasvir/sofosbuvir. Differently, the local prescribing trend (listed in ascending order) was: simeprevir, sofosbuvir/daclatasvir, ledipasvir/sofosbuvir and sofosbuvir, ombitasvir/paritaprevir/ritonavir-dasabuvir. Conclusion: The comparison between local and national prescribing trends have shown differences: ledipasvir/sofosbuvir and ombitasvir/paritaprevir/ritonavir-dasabuvir are the most prescribed therapies respectively in the national and local context. These differences could be justified by population differences, however, a detailed study of the local patient population is needed to confirm genotype and patient population as the only influencing factors for discrepancies. References and/or Acknowledgements: 1. WEF-E 2017'Aggiornamento sui dati nazionali di prescrizione dei DAAs dai registri AIFA' Simona Montilla No conflict of interest